Anterior and posterior retrosplenial cortex employ distinct strategies for egocentric–allocentric transformation in spatial coding - Youran Yang; Xiang Zhang; Xin Yuan; Haiqian Cai; Qichen Cao; Chenglin Miao (Proceedings of the National Academy of Sciences, 2026)
The transformation from egocentric to allocentric spatial coordinates is a critical process in neural spatial computation. The retrosplenial cortex (RSC) is hypothesized to serve as a central hub for this conversion, bridging egocentric perceptual inputs with allocentric representations in hippocampal and parahippocampal circuits. However, the regional and projection-specific organization of this function within the RSC remains poorly defined. In this study, we employed two-photon calcium imaging in freely navigating mice to dissect RSC spatial coding. We identified functional differences along the anteroposterior axis: the anterior RSC (aRSC) was predominantly characterized by egocentric boundary vector (EBV) coding, whereas the posterior RSC (pRSC) exhibited enhanced allocentric boundary representation. And it reveals that egocentric boundary vector cells (EBVCs) in the pRSC possess broader egocentric tuning than those in the aRSC. Despite this, pRSC shows tighter integration of allocentric head direction information, which converges specifically onto specialized conjunctive cells, resulting in a more selective boundary representation. Crucially, this work identifies functional differences along the RSC, where spatial coding transforms from more egocentric in aRSC to more allocentric in pRSC. Furthermore, it defines a specialized RSC to medial entorhinal cortex (MEC) projection pathway that is enriched for these global-tuned, conjunctive neurons, providing the MEC with a highly integrated, world-referenced spatial signal for constructing cognitive maps. Our findings elucidate a functional variance and projection-specific circuitry within the RSC, providing experimental evidence for models of hierarchical spatial processing.